EVALUASI KINERJA PENYELENGGARA IBADAH HAJI DI PROVINSI GORONTALO - Tilome, Arfan A (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2025)
The purpose of this study was to evaluate the performance of the pilgrimage organizers in terms of guidance of the rituals of Hajj, passport services, health services, pelayanaan at Hajj dormitory, transportation services, and baggage service. This type of research is pursued with the model of summative evaluative research, which evaluates the performance of the pilgrimage organizers of aspects of the product using the criteria of excellent, good, poor, and not well indexed on community satisfaction as stipulated in the Decree of the Minister of State for Administrative Reform Republic Indonesia Number 25 of 2004. Required data collected in this study using a questionnaire instrument, interviews, and observations. Key informants in the study were pilgrims Gorontalo province in 2011, 2012, and 2013 as the population of 2,250 people and 10% of the sample population of 225 people.The results of this study revealed that the overall performance of the pilgrimage organizers in Gorontalo is good. Performance shall include the performance of the pilgrimage organizers in terms of guidance of the rituals of Hajj is good, service is good passport, health care is good, pelayanaan at Hajj dormitory is good, service is good transportation, and the performance of the pilgrimage organizers in terms of baggage service is also good. Based on this research it is recommended to both the central and local governments in order to meet the needs of facilities and infrastructure, especially in the Hajj, making a unified service standards, increasing the number of service personnel, as well as speed up service time